Child development one to three [videorecording] - Sears, Twila; Laleman, Joseph P.; Meridian Education Corporation (Bloomington, Ill. Meridian Education Corp., 1990)
Presents the developmental stages of children and details the development of the child during the stages from one to three including interviews with child psychologist and parents of toddlers. Also examined are the new skills that the toddler learns during this period.
Keywords: Child development